The number systems and operations of arithmetic : an explanation of the fundamental principles of mathematics which underlie the understanding and use of arithmetic, designed for in-service training of elementary school teachers and pre-service training of elementary school teacher candidates - Klose, Orval M. (Commonwealth and international library of science and technology, engineering, and liberal studies. Mathematics division., 1966)
The Number Systems and Operations of Arithmetic was written for the single purpose of explaining to elementary school teachers (both in-service and in-training) the nature of those basic principles of mathematics which form the foundations and structural framework of arithmetic, and how the familiar formal algorithms of arithmetic stem from these structural principles.